COBIT 5.0: Capability Level of Information Technology Directorate General of Treasury - Dian Utami Setya; Wella Wella (Universitas Multimedia Nusantara, 2018)
Information system is one of the most important things that can help every companies to improve the performance of their company. The Directorate Generate of the Treasury is one of the government agencies that already use information systems to support their performance to handle the entire transaction of state budgeting and also they provides information systems to serve their users. That system must have a priority of the security and reliability. To ensure that the system has both of the priority, it is necessary to holding of the information systems auditing to ensure that capability level of their governance. The author doing the audit of information system using framework of COBIT 5.0 and doing measurements with Capability Level. EDM 01 (Ensure Governance Framework Setting and Maintenance) and EDM 02 (Ensure Benefits Delivery) are the two main processes of that government needs to do an audit, because they want to make sure that the system can running well and can deliver every benefits to their users. Based on the measurements that have been done using a capability level, both of the main processes are stalled on level 4 and could not reach the level of target on level 5 because there are some activities that cannot going well and can be inhibit the others process to reach their goals. Index Terms— Capability Level, COBIT 5.0, Information Systems, Information Systems Auditing, IT Governance.